DETERMINATION OF OPTIMAL CENTERS FOR LOCATION OF AREAS OF EGGS SUPPLY FOR GANJA-DASHKASAN AND KAZAKH-TOVUZ ECONOMIC REGIONS - SADIKHOVA, MATANAT SHAHIN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The purpose of the article. Most of the products of the main demand among livestock products are perishable products. Along with the requirements attributed to the quality of this category of products, the requirements for their storage distinguish them from other products. This feature is due to the need to maintain the required temperature regime throughout the entire period of existence of perishable products, from the moment of their manufacture to the moment of consumption. Thus, the quality of the transported product is ensured, on which the safety of the population directly depends.Thus, the process of transporting perishable products is considered actual in its essence. This makes it necessary to investigate, analyze and solve existing problems in the specified area. This article is devoted to the problem of transportation of eggs to the supply points of livestock products produced in farms.The methodology and methods used are the theoretical and methodological basis of the research, the works of local and foreign scientists dedicated to the deployment of production forces, the transport provision of cargo transportation, as well as the operation of the collector transport system, scientific literature on statistics, probability, graphs and management theories, economic mathematical modeling.The main scientific innovation put forward is the development of the methodology, mathematical model of the optimal location of supply and reception points in the territory according to the minimum cost of transportation and the maximum profit, and the determination of optimal centers.The result of the research is the determination of the optimal location centers by establishing a mathematical model of the supply points of the eggs belonging to livestock products in Ganja-Dashkasan and Gazakh-Tovuz economic regions. Based on the software developed in the MathCAD computer optimization system, it is possible to determine the coordinates of the optimal location centers of the supply points, which are considered relevant as a large-scale problem in a short period of time. The high accuracy and authenticity of the obtained results indicate the possibility and significance of the wide application of the developed methodology in agriculture.
Keywords: supply point; farm; livestock products; optimal location; transportation of eggs